Nitrenes and nitrenium ions - Falvey, Daniel E., 1961-; Gudmundsdottir, Anna D., 1962- (Wiley series on reactive intermediates in chemistry and biology ;, 2013)
"Nitrenes and Nitrenium ions are reactive intermediates with monovalent nitrogen atoms. These intermediates have diverse reactivity and physical properties, depending on their structure and spin state. The leading experts in nitrene chemistry have contributed to this book to highlight how spectroscopy and calculations have been used to characterize various nitrene intermediates. Emphasizes have also been placed on identifying the diverse methods to form these intermediates. Furthermore, the reactivity of nitrenes and nitrenium ions is discussed in details and how the reactivity can be used in various applications"--